Optical mineralogy - Kerr, Paul F. (New York McGraw-Hill, 1977)
Previously entered under A. F. Rogers and P. F. Kerr; 1st ed. published under title: Thin-section mineralogy.Includes bibliographies and index.
Keywords: Optical mineralogy